2006
DOI: 10.1093/schbul/sbl060
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Endophenotypes of Schizophrenia: The Viability of Selected Candidate Measures

Abstract: In an effort to reveal susceptibility genes, schizophrenia research has turned to the endophenotype strategy. Endophenotypes are characteristics that reflect the actions of genes predisposing an individual to a disorder, even in the absence of diagnosable pathology. Individual endophenotypes are presumably determined by fewer genes than the more complex phenotype of schizophrenia and would, therefore, reduce the complexity of genetic analyses. Unfortunately, despite there being rational criteria to define a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
393
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(413 citation statements)
references
References 332 publications
(380 reference statements)
12
393
1
7
Order By: Relevance
“…There is increasing evidence that the pathophysiology of schizophrenia entails both high-level cognitive impairments as well as (and perhaps as a consequence of) low-level sensory processing deficits across sensory modalities (Butler and Javitt, 2005;Foxe et al, 2005;Javitt et al, 1999). For example, previous research has consistently shown that the MMN is impaired in schizophrenia patients (Catts et al, 1995;Javitt et al, 1993Javitt et al, , 1998Shelley et al, 1991;Shutara et al, 1996; for review see Turetsky et al, 2007), and this was again the case for our patients at protocol onset (Figure 2). Interestingly, the greater the MMN impairment, the lower are the Global Assessment of Functioning Scale ratings, suggesting that MMN is linked to global impairments in everyday functioning in schizophrenia patients (Kawakubo and Kasai, 2006;Light and Braff, 2005a, b).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…There is increasing evidence that the pathophysiology of schizophrenia entails both high-level cognitive impairments as well as (and perhaps as a consequence of) low-level sensory processing deficits across sensory modalities (Butler and Javitt, 2005;Foxe et al, 2005;Javitt et al, 1999). For example, previous research has consistently shown that the MMN is impaired in schizophrenia patients (Catts et al, 1995;Javitt et al, 1993Javitt et al, , 1998Shelley et al, 1991;Shutara et al, 1996; for review see Turetsky et al, 2007), and this was again the case for our patients at protocol onset (Figure 2). Interestingly, the greater the MMN impairment, the lower are the Global Assessment of Functioning Scale ratings, suggesting that MMN is linked to global impairments in everyday functioning in schizophrenia patients (Kawakubo and Kasai, 2006;Light and Braff, 2005a, b).…”
Section: Discussionsupporting
confidence: 67%
“…NMDA receptor antagonists block MMN generation in both primates (Javitt et al, 1996) and humans (Umbricht et al, 2000), suggesting that the MMN reflects current flow through NMDA channels. The amplitude of MMN is known to be decreased in schizophrenia (Catts et al, 1995;Javitt et al, 1993Javitt et al, , 1998Shelley et al, 1991;Shutara et al, 1996; for review see Turetsky et al, 2007), further implicating impaired NMDA function in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothetically, alterations in hippocampal inhibitory interneurons may underlie the observed deficits in the NR1 mutants. CA3 interneurons have been suggested to be the crucial final neurons mediating hippocampal sensory gating (Turetsky et al, 2006). Repeated but not single application of NMDAR antagonists decreased the number of interneurons expressing parvalbumin (a Ca 2 + -binding protein expressed by a subclass of interneurons) in the hippocampus of rodents (Keilhoff et al, 2004;Cunningham et al, 2006).…”
Section: Auditory Gatingmentioning
confidence: 99%
“…For example, there is limited evidence for co-segregation with illness, let alone heritability for many neurophysiological and neurocognitive measures that have been suggested as schizophrenia endophenotypes. 9,10 The extent to which this matters depends upon the use to which an endophenotype is being put and it is helpful to consider the possibilities in some detail.…”
mentioning
confidence: 99%
“…First, it is often not clear how stateindependent many of the measures proposed really are, with the potential for contamination not just by fluctuations in course of illness and drug treatment, but also by factors such as smoking and menstrual cycle phase. 9,11 Second, there are uncertainties about reliability and particularly inter-laboratory variation for many of the methods espoused. For example, there are no generally agreed protocols for reliably eliciting electrophysiological deficits in pre-pulse inhibition (PPI) and P50 sensory gating, which have been proposed as endophenotypes in schizophrenia, as well as concerns regarding test-retest reliability.…”
mentioning
confidence: 99%